2014
DOI: 10.2341/13-116-s
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Approach to Delayed Treatment of Traumatic Teeth Injuries Involving Extrusive Luxation, Avulsion and Crown Fracture

Abstract: A 12-year-old boy with extrusion of the maxillary right central incisor, uncomplicated fracture of the left central incisor, avulsion of the mandibular right and left central incisors, and crown fracture of the mandibular right lateral incisor presented to the Kocaeli University Department of Pediatric Dentistry 20 days after sustaining the traumatic injuries. Orthodontic repositioning of the extrusive maxillary right central incisor was planned. Additionally, this tooth was necrotic and needed root canal trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 17 publications
0
20
0
1
Order By: Relevance
“…21 Studies indicate that pulp necrosis after extrusive luxation occurs in between 26 and 43% 24,25 of cases; this occurred in two studies selected for this review. 20,22 Andreasen and Pedersen 25 found a significantly higher level of necrosis in mature teeth pulp; however, Lee et al 24 reported the degree of extrusion to be the main factor responsible for the pulp necrosis and the endodontic obliteration, in the case of traumatic pulp extrusion.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…21 Studies indicate that pulp necrosis after extrusive luxation occurs in between 26 and 43% 24,25 of cases; this occurred in two studies selected for this review. 20,22 Andreasen and Pedersen 25 found a significantly higher level of necrosis in mature teeth pulp; however, Lee et al 24 reported the degree of extrusion to be the main factor responsible for the pulp necrosis and the endodontic obliteration, in the case of traumatic pulp extrusion.…”
Section: Discussionmentioning
confidence: 98%
“…According to the included studies, 12,[20][21][22] there is insufficient evidence that one type of treatment is a superior option, although there are favorable and unfavorable for each option proposed treatment points.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The anterior tooth, involving enamel and dentin, is the most frequent tooth affected, in which the coral fractures represents 65-75% of all dental traumas. [1][2][3] According to a review, for the permanent dentition the crown fractures without pulp exposure is the most common injury described in most studies. 4 Also, the maxillary central incisor is the most frequently affect teeth.…”
Section: Introductionmentioning
confidence: 99%